2013
DOI: 10.1002/dmrr.2417
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gestational diabetes on circadian rhythms of children and their association with fetal adiposity

Abstract: Fetal adiposity correlated with a worse circadian rhythm regulation in ODM. In addition, ODM insulin-treated showed a disturbed pattern of the circadian function index of temperature activity at 6 months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…However, we previously reported impairment in some parameters that define temperature maturation and the CFI at 6 months in the GDM+insulin group. 27 Baddock et al 28 reported differences in mean rectal and skin temperatures in infants bed-sharing with their parents with respect to when they were sleeping on their own in a cot. In order to exclude this potential confounding factor, all the babies slept in a cot in the parents' room and none of them shared the bed.…”
Section: Discussionmentioning
confidence: 99%
“…However, we previously reported impairment in some parameters that define temperature maturation and the CFI at 6 months in the GDM+insulin group. 27 Baddock et al 28 reported differences in mean rectal and skin temperatures in infants bed-sharing with their parents with respect to when they were sleeping on their own in a cot. In order to exclude this potential confounding factor, all the babies slept in a cot in the parents' room and none of them shared the bed.…”
Section: Discussionmentioning
confidence: 99%
“…While it is known that disrupted circadian rhythms can be detrimental to reproductive success (Dolatshad et al, 2005;Mahoney, 2010), it remains largely unknown how they change from the non-pregnant state to pregnancy. Understanding the role of circadian rhythms in regulating both behavior and tissue-specific circadian function during the estrous cycle and in pregnancy is an essential first step toward elucidating the underlying mechanisms associated with infertility and pregnancy complications, which are more prevalent in women with disrupted circadian rhythms (Goldberg et al, 2012;Nisa et al, 2018;Pappa et al, 2013;Zornoza-Moreno et al, 2013). We hypothesize that circadian timekeeping during late pregnancy influences mouse behavior and reproductive tissue circadian function in preparation for labor.…”
Section: Introductionmentioning
confidence: 99%
“…In further work Zornoza-Moreno et al (2013) examined development of infant rhythm from the neonatal period through 6 months of age. Few investigators jointly study maternal and infant rhythm.…”
Section: Introductionmentioning
confidence: 99%